Utilization of Blockchain technologies for enhanced transparency and traceability in the Supply Chain - Erik, Fohlin; Johan, Ysberg (My University, 2019)
Utilization of blockchain technology for enhanced transparency and traceability in supply chains is in focus for this research study. The globalization of markets and new information technologies have presented companies with both new opportunities and challenges. Where increased industry competition and continuously changing customer demands are pushing companies in manufacturing industry into becoming increasingly responsive and productive. In a rapidly shifting competitive landscape, outsourcing on one hand may enable higher productivity and responsiveness of a company's supply chain. On the other hand, it may result in a disintegrated supply chain, where transparency and traceability becomes inhibited. Inefficiencies such as information asymmetries, fragmentation of data, desynchronization between supply chain actors and activities lead to reduced supply chain performance. The area of blockchain technologies have experienced increased attention the last few years as a potential solution for mitigating these inefficiencies. Where a blockchain can be described as a tamper evident and tamper resistant digital ledger, implemented in a distributed fashion. As blockchain solutions could potentially enable enhanced transparency and complete traceability, it becomes interesting for investigation. The purpose of the study has thus been to evaluate how the emerging blockchain technologies can ensure enhanced transparency and traceability in the supply chains of the manufacturing industry. Four use-case scenarios in a large global manufacturing firm have been studied, counterfeiting and piracy; remanufacturing; warranty; and export control and clearance of dual-use goods. The characteristics of blockchains as a nascent technology have been examined. Furthermore, the characteristics of the generic supply chain in the manufacturing industry have also been mapped. Data have been gathered through literature searchers and interviews with industry experts, where empirical findings have been analysed using two different frameworks. Firstly, an evaluation tree has been used to establish whether there is an actual need for a blockchain solution. Secondly, an SFA (suitability, feasibility, acceptability) framework was used, where the business potential of each individual use-case scenario in relation to a blockchain solution have been analysed. The findings of this study contribute to previous research by indicating that blockchain technologies could provide substantial benefits primarily in two of the four investigated use-case scenarios. Utilization of blockchain technologies for enhanced transparency and traceability in supply chains will most likely be key for success, where collaboration between supply chain actors and organizations already addressing business potential of blockchains will most likely be a critical enabler for proficient use. As well as for overcoming the inherent technical limitations, such limited interoperability, speed and resource efficiency of current blockchain technologies.